KLF4 is a key determinant in the development and progression of cerebral cavernous malformations. Issue 1 (26th November 2015) - Cuttano, Roberto; Rudini, Noemi; Bravi, Luca; Corada, Monica; Giampietro, Costanza; Papa, Eleanna; Morini, Marco Francesco; Maddaluno, Luigi; Baeyens, Nicolas; Adams, Ralf H; Jain, Mukesh K; Owens, Gary K; et al.
Abstract: Cerebral cavernous malformations (CCMs) are vascular malformations located within the central nervous system often resulting in cerebral hemorrhage. Pharmacological treatment is needed, since current therapy is limited to neurosurgery. Familial CCM is caused by loss‐of‐function mutations in any of Ccm1, Ccm2, and Ccm3 genes. CCM cavernomas are lined by endothelial cells (ECs) undergoing endothelial‐to‐mesenchymal transition (EndMT). This switch in phenotype is due to the activation of the transforming growth factor beta/bone morphogenetic protein (TGFβ/BMP) signaling. However, the mechanism linking Ccm gene inactivation and TGFβ/BMP‐dependent EndMT remains undefined. Here, we report that Ccm1 ablation leads to the activation of a MEKK3‐MEK5‐ERK5‐MEF2 signaling axis that induces a strong increase in Kruppel‐like factor 4 (KLF4) in ECs in vivo . KLF4 transcriptional activity is responsible for the EndMT occurring in CCM1‐null ECs. KLF4 promotes TGFβ/BMP signaling through the production of BMP6. Importantly, in endothelial‐specific Ccm1 and Klf4 double knockout mice, we observe a strong reduction in the development of CCM and mouse mortality. Our data unveil KLF4 as a therapeutic target for CCM. Synopsis: Current therapy for cerebral cavernous malformation (CCM) therapy is limited to neurosurgery. Transcription factor KLF4 is found to be a crucial determinant for the development of cavernomas and thus a future therapeutic target. KLF4 is strongly upregulated in endothelial cells in the absence of any of the three CCM genes. The endothelial‐to‐mesenchymal transition observed in endothelial cells null for CCM1 is induced by KLF4. KLF4 activates TGFβ/BMP signaling by increasing Bmp6 expression in endothelial cells in the absence of CCM1. The development and progression of cavernomas is strongly reduced upon genetic Klf4 inactivation. KLF4 is a strong candidate as a novel target for the pharmacological treatment of CCM, since its inactivation reduces mouse mortality associated to this disease by 75%. Abstract : Current therapy for cerebral cavernous malformation (CCM) therapy is limited to neurosurgery. Transcription factor KLF4 is found to be a crucial determinant for the development of cavernomas and thus a future therapeutic target.